Determining the Knowledge Levels and Opinions of Athletes who is age Under-16 in Different Branches about Doping and Ergogenic Aids - Ceylan, Abdil; Çalık, Fehmi; Geri, Serdar; Şen, Murat; Ece, Cuma; Sumer, Mehmet (Progress in Nutrition, 2021)
Study Objectives: The study aimed to evaluate the knowledge levels and opinions of athletes under 16 years of age about doping and ergogenic aids in different branches. The fact that there are no studies in the literature on the knowledge and opinions of athletes under the age of 16 on doping and ergogenic aids has encouraged us to the study. Methods: The sample of the study consists of 392 athletes under 16 years of age in different sports branches. In the study, a questionnaire consisting of 5 likert and 26 questions about doping substances and ergogenic aids was applied to the athletes by Eröz (2007). Results: As a result of the analysis of the obtained findings with the Chi-square test, it was determined that as the age of the athletes increased, the belief that the athlete used doping increased with the fear of losing. It has been determined that as the family income increases, the tendency to try every way to be successful does not decrease significantly, and athletes with low family income are more willing to try every way to be successful. As the education of the athlete’s parents increased, the belief that the use of doping harmed the Fair-Play spirit in sports and that doping leads to unfair competition has been increased. Conclusion: The study revealed that there is a need to reinforce the doping knowledge of athletes. It has been concluded that certain socio-economic conditions are determinants in the use of doping by athletes and that they shape their tendency towards doping. Therefore, it is thought that the trainers, managers, athlete families and athletes about the negative effects of doping use on athlete health is of great importance.